AN AUDIT OF INTRAVENOUS MAINTENANCE FLUIDS PROTOCOLS AGAINST THE NATIONAL INSTITUTE FOR HEALTH AND CARE EXCELLENCE GUIDELINE NG29 (The Research of Medical Science Review, 2025)
This project aimed to determine adherence to NG29, in pediatric patients, receiving at least 24 hours of IV maintenance fluids in the Gujranwala Medical College Teaching Hospital. The main goal is to present a current 2023 perspective on GMC &current practice of prescribing and treating pediatric fluids. The purpose of this audit is to determine whether giving IV fluids to minors (those aged over 16 years old and those aged over 4 weeks) is safe and meets quality standards. Result: Hypotonic fluids are now not prescribed in children undergoing post-operative paediatric IV maintenance fluids, though they are still being given suboptimal surveillance. In the future, it will be important to monitor children more closely utilizing fluids.